New Samarium(III), Gadolinium(III), and Dysprosium(III) Complexes of Coumarin-3-Carboxylic Acid as Antiproliferative Agents. (27th February 2007) - Kostova, Irena; Momekov, Georgi; Stancheva, Peya
Abstract : New complexes of samarium(III), gadolinium(III), and dysprosium(III) with coumarin-3-carboxylic acid (HCCA) were prepared by the reaction of the ligand with respective metal nitrates in ethanol. The structures of the final complexes were determined by means of physicochemical data, elemental analysis, IR and Raman spectra. The metal-ligand binding mode in the new Ln(III) complexes of coumarin-3-carboxylic acid was elucidated. The vibrational study gave evidence for bidentate coordination ofCCA − to Ln(III) ions through the carbonylic oxygen and the carboxylic oxygen atoms. The complexes were tested for antiproliferative activitiy on the chronic myeloid leukemia-derived K-562, overexpressing the BCR-ABL fusion protein. Cytotoxicity towards tumor cells was determined for a broad concentration range. The samarium salt exerted a very weak antiproliferative effect on these cells. This is in contrast to the lanthanide complexes, especially samarium complex, which exhibited potent antiproliferative activity. The present study confirms our previous observations that the lanthanide complexes of coumarins exhibit antiproliferative activity towards K-562 cell line.